Histopathological Features of the Pancreas in Alloxan-Induced Diabetic White Rats Treated with Bandotan (Ageratum conyzoides L.) Extract - Hasibuan, Fitriah Parmadami; Novriani, Erida; Simanjuntak, Nerly Juli Pranita (CV. Nusantara Scientific Medical, 2025)
Damage to pancreatic β-cells can lead to hyperglycemia, a hallmark of diabetes mellitus. Ageratum conyzoides L. (bandotan), a plant from the Asteraceae family, is traditionally used in herbal medicine due to its rich content of secondary metabolites. This study aimed to evaluate the histopathological profile of pancreatic tissue in alloxan-induced diabetic rats following treatment with ethanol extract of bandotan leaves. The research employed a true experimental design with a posttest-only control group. A total of 24 white rats were randomly divided into six groups: normal, negative control (aquadest + alloxan), positive control (glibenclamide 0.65 mg/kg BW), and three treatment groups receiving bandotan extract at doses of 100, 200, and 400 mg/kg BW, respectively. Bandotan leaves (4–5 kg) were extracted using ethanol, and histopathological observations were performed under a light microscope at 100x and 400x magnification. Pancreatic damage was scored and analyzed using descriptive statistics. The mean pancreatic damage scores were as follows: negative control group = 1.25; positive control group = 1.00; 100 mg/kg BW group = 1.00; 200 mg/kg BW group = 0.25; 400 mg/kg BW group = 0.00; and normal group = 0.00. The results indicate that the 400 mg/kg BW dose of Ageratum conyzoides L. extract was the most effective in preventing pancreatic damage, with histological features comparable to those of the normal group.